Cost of economic growth: an analysis of trends and prospects of application of CT + AC models in large industries in the district of Tarapoto, San Martin, 2014 (Gaceta Técnica, 2018)
The aim of this study is to analyze the trends and prospects of application of models of Technological Change (CT) + Accumulation of Capital (AC) on productivity and human capital industries Tarapoto, San Martin, 2014. The type of study was descriptive and longitudinal cutting trends. Non-probability sampling with a sample of 8 companies was used. The survey use categories and related codes Likert scale. The instrument was validated by Cronbach’s Alpha reached 0.85. The information was processed using the program SPSS. The statistical test used was Wilcoxon and Mc Newmar. The results show that technological change influenced production (29%) increased by activating stocks and inventories. They arranged for new technologies due to the incorporation of research and development (21%). They used more competitive edge production factors improving productivity (27%). They took advantage of the opportunity cost through new investment options (22%). The accumulation of asset disposal of human capital (29%) and the production function (21%) capital. The study shows that the model Cost of Economic Growth (EEC) shows positive trends in economic growth in the region of San Martín, since technological change influences productivity (0.018 with a p value
Keywords: cost of economic growth; technological change; accumulation of capital